High-strength rare earth magnesium alloy and preparation process thereof

CN120366612BActive Publication Date: 2026-10-20CHONGQING UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510595967.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-09
Publication Date
2026-10-20
Estimated Expiration
2045-05-09

AI Technical Summary

Technical Problem

在实际生产过程中,难以精确控制LPSO相的形态、尺寸和分布,这在一定程度上影响了镁合金性能的稳定性和可重复性,限制了镁合金性能的进一步提升

Benefits of technology

[0028]1、本发明提出了一种高强稀土镁合金及其制备工艺,通过在镁合金中引入Sm元素,并结合热挤压和热处理工艺,对合金中的长周期堆垛有序相(LPSO相)进行有效调控。LPSO相在合金中的数量显著增加,尺寸变得更细小,且分布更加弥散。这种微观结构的优化显著提升了镁合金的力学性能,使其抗拉强度达到385-417MPa,成功制备出高强度镁合金。这一工艺充分利用了Sm元素的特性与先进加工技术的协同作用,为镁合金性能的提升提供了全新的解决方案。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120366612B_ABST
    Figure CN120366612B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of metal materials, and relates to a high-strength rare earth magnesium alloy and a preparation process thereof. The preparation process comprises the following steps: smelting: smelting pure magnesium, Mg-25Ni intermediate alloy, Mg-30Gd intermediate alloy and Mg-30Sm intermediate alloy into alloy ingots; homogenization treatment: after the surface of the alloy ingot is polished, the alloy ingot is wrapped with aluminum foil, then the alloy ingot is buried in a middle crucible with graphite powder, the crucible is placed in a heat treatment furnace, the temperature is raised to 300 DEG C and kept for 1 hour, then the temperature is raised to 530 DEG C and kept for 12 hours, and after the keeping, the alloy ingot is water-cooled; hot extrusion: the alloy ingot after the homogenization treatment is processed into a cylindrical blank, the blank and a mold are preheated, then the blank is loaded into an extruder for normal extrusion; aging treatment: the rod after the hot extrusion is cut into a cylindrical rod, then the rod is wrapped with aluminum foil, the rod is buried in a middle crucible with graphite powder, and the rod is kept at 200 DEG C for 26 hours, and after the keeping, the rod is water-cooled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metallic materials technology and relates to a high-strength rare earth magnesium alloy and its preparation process. Background Technology

[0002] Magnesium alloys, as the lightest structural materials currently used in engineering applications, have shown great promise in a wide range of fields, including aerospace, automotive manufacturing, and electronics, thanks to their significant advantages such as high specific strength and high specific stiffness. However, the relatively low absolute strength of magnesium alloys has greatly limited their further promotion and application in many scenarios. Therefore, developing magnesium alloy materials with higher strength has become a highly anticipated and key research direction in the field of magnesium alloys.

[0003] In the research process of magnesium alloy alloying, the addition of rare earth elements has been proven to be an effective strengthening method. Taking Mg-Ni magnesium alloys as an example, the addition of appropriate amounts of rare earth elements can produce multiple positive effects. On the one hand, the addition of rare earth elements can effectively refine the alloy grains, reducing grain size and increasing the number of grain boundaries, thereby enhancing the mechanical properties of the alloy. On the other hand, rare earth elements can promote the formation of long-period packed phases (LPSO phases). As a special strengthening phase, the LPSO phase plays an important role in magnesium alloys. It can effectively hinder dislocation movement, increase the resistance to dislocation movement, and enable the alloy to withstand greater stress without plastic deformation. At the same time, the formation of the LPSO phase can further refine the grains, improve the mechanical properties of magnesium alloys from multiple dimensions, and significantly increase the strength of the alloy.

[0004] While the addition of rare earth elements has achieved some improvement in the strength of magnesium alloys, several problems remain to be solved. First, the amount of rare earth elements added is typically large. Rare earth elements are rare metals with high mining and refining costs; adding large amounts significantly increases the production cost of the alloy, hindering large-scale industrial production and widespread application of magnesium alloys. Second, existing technologies have limited control over the LPSO phase. In actual production, it is difficult to precisely control the morphology, size, and distribution of the LPSO phase, which affects the stability and repeatability of magnesium alloy properties, limiting further performance improvements.

[0005] Therefore, how to improve the precise control of the LPSO phase to achieve better performance of magnesium alloys has become an important challenge in the current field of magnesium alloy research, and it is also the key problem that this patent application aims to solve. Summary of the Invention

[0006] In view of this, the purpose of the present invention is to provide a high-strength rare earth magnesium alloy and its preparation process. By adding the rare earth element samarium (Sm) to the Mg-Ni-Gd alloy and combining hot extrusion and heat treatment processes, the grain size of the magnesium alloy is refined, and the morphology and distribution of the LPSO phase in the magnesium alloy are controlled, thereby improving the strength of the magnesium alloy.

[0007] To achieve the above objectives, the present invention provides the following technical solution:

[0008] A preparation process for a high-strength rare-earth magnesium alloy includes the following steps:

[0009] (1) Smelting: Pure magnesium, Mg-25Ni master alloy, Mg-30Gd master alloy and Mg-30Sm master alloy are smelted into alloy ingots;

[0010] (2) Homogenization treatment: After the surface of the alloy ingot is polished, it is wrapped with aluminum foil, then graphite powder is used to embed it in the crucible, and the crucible is placed in the heat treatment furnace. The temperature is raised to 300℃ and held for 1 hour, then raised to 530℃ and held for 12 hours. After the holding is completed, it is water-cooled.

[0011] (3) Hot extrusion: The homogenized alloy ingot is processed into a cylindrical billet, which is preheated together with the die, and then loaded into the extrusion press for positive extrusion. The extrusion parameters are: extrusion temperature 420℃, extrusion speed 1.5-2.5m·min -1 The extrusion ratio is 10.24:1, and the material is water-cooled after extrusion.

[0012] (4) Aging treatment: Cut the hot-extruded bar into cylindrical bars, wrap them with aluminum foil, bury them in a crucible with graphite powder, and keep them at 200℃ for 26 hours. After the heat preservation is completed, cool them with water.

[0013] Further, step (1) includes the following steps:

[0014] a) Alloy raw material preparation: pure magnesium, Mg-25Ni master alloy, Mg-30Gd master alloy and Mg-30Sm master alloy are machined into blocks and the oxide film on their surface is ground off.

[0015] b) Heating the resistance furnace: First, heat the resistance furnace to 600℃, and after the temperature stabilizes, heat it to 750℃. At the same time, dry and preheat the crucible.

[0016] c) Adding intermediate alloys: After the crucible is preheated to above 300°C, pure magnesium is placed in the crucible and the crucible is placed in an electric resistance furnace. A protective atmosphere of SF6+CO2 is introduced. After the pure magnesium melts, Mg-25Ni, Mg-30Gd and Mg-30Sm intermediate alloys are added in sequence. After they are completely melted, the furnace temperature is adjusted to 730°C and held for 10 minutes.

[0017] d) Stirring and impurity removal: Stir for 5 minutes after power is off, then heat the resistance furnace to 720℃, let it stand for 2 minutes, and then filter out the impurities;

[0018] e) Cooling: Remove the crucible and place it in cold water to cool to room temperature, then remove the alloy ingot.

[0019] Furthermore, in step (1)a), the purity of the pure magnesium is 99.99 wt.%.

[0020] Further, in step (1)c), the volume ratio of the protective atmosphere SF6+CO2 is 1:99.

[0021] Furthermore, in step (1)d), a long-handled strainer is used to filter out impurities.

[0022] Furthermore, in step (2), the time to raise the temperature to 300°C is 2 hours, and the time to raise the temperature to 530°C is 2 hours.

[0023] Furthermore, in step (3), the preheating temperature of the mold and the alloy billet is 420°C, and the preheating time is 2 hours.

[0024] Further, in step (3), the homogenized alloy ingot is processed into a cylindrical billet with a diameter of 80mm; in step (4), the hot-extruded bar is cut into cylindrical bars with a length of 70mm.

[0025] Furthermore, the atomic percentages of each element in the alloy composition of the alloy ingot are as follows: Ni: 0.75%, Gd: 1.0%, Sm: 0.2-0.8%, with the remainder being Mg.

[0026] A high-strength rare-earth magnesium alloy, prepared by the aforementioned process, has the following atomic percentages of each element in its alloy composition: Ni: 0.75%, Gd: 1.0%, Sm: 0.2-0.8%, with the remainder being Mg.

[0027] The beneficial effects of this invention are as follows:

[0028] 1. This invention proposes a high-strength rare-earth magnesium alloy and its preparation process. By introducing Sm element into the magnesium alloy and combining hot extrusion and heat treatment processes, the long-period stacked ordered phase (LPSO phase) in the alloy is effectively controlled. The quantity of LPSO phase in the alloy increases significantly, its size becomes smaller, and its distribution becomes more dispersed. This optimization of the microstructure significantly improves the mechanical properties of the magnesium alloy, enabling its tensile strength to reach 385-417 MPa, successfully preparing a high-strength magnesium alloy. This process fully utilizes the synergistic effect of the properties of Sm element and advanced processing technology, providing a novel solution for improving the performance of magnesium alloys.

[0029] 2. Sm plays multiple important roles in this technical solution. First, as a light rare earth element, Sm has an atomic radius similar to Gd and a high solid solubility in magnesium alloys (approximately 5.8 wt.%), effectively replacing Gd in the LPSO phase and promoting the formation of more LPSO phase. After adding Sm, the alloy's strength is significantly improved through three mechanisms: solid solution strengthening, second-phase strengthening, and grain refinement strengthening. Second, the cost of Sm is far lower than that of the expensive rare earth element Gd. By adding Sm, this invention reduces the Gd content to only 1.0 at.%, significantly reducing the demand for high-cost rare earth elements and thus significantly lowering the production cost of magnesium alloys. This "low-cost substitution" strategy not only improves performance but also achieves economic benefits, laying the foundation for the large-scale application of magnesium alloys.

[0030] 3. The innovation of this technical solution lies in the precise control of the LPSO phase using Sm elements, breaking through the bottleneck between traditional magnesium alloy strength improvement and cost control. By controlling the quantity and distribution of the LPSO phase, the alloy strength is significantly improved; simultaneously, the design of reducing Gd element usage effectively optimizes the cost structure. The uniqueness of this method lies in its ability to enhance the mechanical properties of magnesium alloys while simultaneously increasing their application potential in aerospace, automotive manufacturing, and other fields. The practicality of the process is not only reflected in its dual advantages in performance and cost but also in its strong operability and ease of industrialization. This innovative and practical technical solution opens up new avenues for the development and application of high-strength magnesium alloys and has broad market prospects.

[0031] Other advantages, objectives, and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination, or may be learned from practice of the invention. The objectives and other advantages of the invention can be realized and obtained through the following description. Attached Figure Description

[0032] To make the objectives, technical solutions, and advantages of the present invention clearer, the preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings, wherein:

[0033] Figure 1 A flowchart of the preparation process of a high-strength rare earth magnesium alloy;

[0034] Figure 2 The tensile stress-strain curves of the magnesium alloys in Examples 1-4 and Comparative Example 1 are shown.

[0035] Figure 3The figures show the microstructures of magnesium alloys in Examples 1-4 and Comparative Example 1, where the grayish-white phase is the LPSO phase; Figure (a) is Comparative Example 1, Figure (b) is Example 1, Figure (c) is Example 2, Figure (d) is Example 3, and Figure (e) is Example 4.

[0036] Figure 4 for Figure 3 Phase area fraction diagram of the LPSO phase; from left to right, they are Comparative Example 1, Example 1, Example 2, Example 3 and Example 4. Detailed Implementation

[0037] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments are only schematic representations of the basic concept of the present invention. Unless otherwise specified, the following embodiments and features can be combined with each other.

[0038] The accompanying drawings are for illustrative purposes only and are schematic diagrams, not actual pictures. They should not be construed as limiting the invention. To better illustrate the embodiments of the invention, some parts in the drawings may be omitted, enlarged, or reduced, and do not represent the actual product dimensions. It is understandable to those skilled in the art that some well-known structures and their descriptions may be omitted in the drawings.

[0039] In the accompanying drawings of the embodiments of the present invention, the same or similar reference numerals correspond to the same or similar components. In the description of the present invention, it should be understood that if terms such as "upper," "lower," "left," "right," "front," and "rear" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the drawings, they are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, the terms used to describe positional relationships in the drawings are only for illustrative purposes and should not be construed as limiting the present invention. For those skilled in the art, the specific meaning of the above terms can be understood according to the specific circumstances.

[0040] Please see Figure 1 This describes a preparation process for a high-strength rare-earth magnesium alloy, which specifically includes the following steps:

[0041] 1) Smelting:

[0042] ① Alloy raw material preparation: Machining the raw materials: pure magnesium (99.99 wt.%), Mg-25Ni (wt.%) master alloy, Mg-30Gd (wt.%) master alloy, and Mg-30Sm (wt.%) master alloy into appropriately sized blocks, and polishing off the oxide film on their surface with coarse sandpaper. After the alloy is polished to a bright shine, it is packaged in a sealed bag for later use.

[0043] ② Heating the resistance furnace: Set the temperature control program for the resistance furnace, first heat the resistance furnace to 600℃, and after the temperature inside the furnace stabilizes, heat the resistance furnace to 750℃. At the same time, dry and preheat the crucible coated with boron nitride release agent.

[0044] ③ Adding intermediate alloys: After the crucible is completely dried and preheated to above 300℃, place pure magnesium in the crucible and then place the crucible in the resistance furnace, and simultaneously introduce a protective atmosphere of SF6+CO2 (volume ratio of about 1:99). After the pure magnesium is completely melted, add the three intermediate alloys Mg-25Ni (wt.%), Mg-30Gd (wt.%), and Mg-30Sm (wt.%) to the stainless steel crucible in sequence. After they are completely melted, adjust the furnace temperature to 730℃ and hold for 10 minutes.

[0045] ④ Stirring and impurity removal: After turning off the power to the resistance furnace, use an electric stirrer to stir from bottom to top for 5 minutes to make the alloy melt as uniform as possible. After the resistance furnace is heated to 720°C and left to stand for 2 minutes, use a long-handled strainer to filter out impurities.

[0046] ⑤ Cooling: After stirring and removing impurities, take out the crucible and slowly place it into cold water for water cooling. After cooling to room temperature, take out the alloy ingot.

[0047] 2) Homogenization treatment: After the surface of the alloy ingot obtained by melting is polished, it is wrapped with aluminum foil, and then graphite powder is used to completely embed it in a stainless steel crucible. The crucible is placed in a heat treatment furnace, and the temperature is set to rise from room temperature to 300℃ for 2 hours and hold for 1 hour. Then the temperature is raised to 530℃ for 2 hours and held for 12 hours. After the holding is completed, it is taken out and water-cooled.

[0048] 3) Hot extrusion: The homogenized alloy ingot is machined into cylindrical billets with a diameter of 80mm. The alloy billets and the die are preheated at 420℃ for 2 hours. After preheating, the die and alloy billets are quickly loaded into the extrusion press for positive extrusion. After extrusion, cooling is performed using water cooling. The extrusion parameters are as follows: Extrusion temperature: 420℃, Extrusion speed: 1.5-2.5m·min -1 Extrusion ratio: 10.24:1;

[0049] 4) Aging treatment: Cut the bar obtained after hot extrusion into cylindrical bars with a length of 70mm. Wrap the cut bars in aluminum foil and then cover them with graphite. Place them in a crucible and keep them at 200℃ for 26 hours. After the heat treatment is completed, take them out and cool them with water.

[0050] A high-strength rare earth magnesium alloy was prepared by the above-mentioned preparation process. The atomic percentage of each element in the alloy composition is as follows: nickel (Ni): 0.75%, gadolinium (Gd): 1.0%, samarium (Sm): 0.2-0.8%, and the remainder is magnesium and other unavoidable impurities.

[0051] The principle behind the Ni / Gd element ratio design in this application is that when the atomic percentages of Ni and Gd are 3:4, the LPSO phase in the alloy is most abundant and most dispersed. The principle behind adding Sm is that simultaneously adding different rare earth elements to a magnesium alloy reduces the solid solubility of the rare earth elements, thereby increasing the amount of precipitated LPSO phase. Furthermore, the LPSO phase exhibits mutual substitution of rare earth elements, further promoting LPSO precipitation. Sm and Gd have similar atomic radii, and Sm has the highest solid solubility among light rare earth elements in magnesium alloys (approximately 5.8 wt.%). Therefore, Sm can effectively substitute Gd for Gd in the LPSO phase, promoting the formation of more LPSO phase.

[0052] Example 1:

[0053] The technical solution of this embodiment is as follows:

[0054] (1) In terms of atomic percentage, the elemental composition of the high-strength rare earth magnesium alloy in this embodiment includes: Ni: 0.75%, Gd: 1.0%, Sm: 0.2%, with the balance being Mg and other unavoidable impurities.

[0055] (2) The preparation method of the high-strength rare earth magnesium alloy in this embodiment includes the following process:

[0056] 1) Smelting:

[0057] ① Alloy raw material preparation: The total weight of each batch is 1.5 kg. The burn loss ratio is adjusted according to the type and content range of alloy elements during batching. The raw materials: pure magnesium (99.99 wt.%), Mg-25Ni (wt.%) master alloy, Mg-30Gd (wt.%) master alloy, and Mg-30Sm (wt.%) master alloy are machined into appropriately sized blocks, and the oxide film on the surface is removed with coarse sandpaper. After the alloy is polished to a bright finish, it is packaged in sealed bags for later use.

[0058] ② Heating the resistance furnace: Set the temperature control program for the resistance furnace, first heat the resistance furnace to 600℃, and after the temperature inside the furnace stabilizes, heat the resistance furnace to 750℃. At the same time, dry and preheat the crucible coated with boron nitride release agent.

[0059] ③ Adding intermediate alloys: After the crucible is completely dried and preheated to above 300℃, place pure magnesium in the crucible and then place the crucible in the resistance furnace, and simultaneously introduce a protective atmosphere of SF6+CO2 (volume ratio of about 1:99). After the pure magnesium is completely melted, add the three intermediate alloys Mg-25Ni (wt.%), Mg-30Gd (wt.%), and Mg-30Sm (wt.%) to the stainless steel crucible in sequence. After they are completely melted, adjust the furnace temperature to 730℃ and hold for 10 minutes.

[0060] ④ Stirring and impurity removal: After turning off the power to the resistance furnace, use an electric stirrer to stir from bottom to top for 5 minutes to make the alloy melt as uniform as possible. After the resistance furnace is heated back to 720℃ and left to stand for 2 minutes, use a long-handled strainer to filter out impurities.

[0061] ⑤ Cooling: After stirring and removing impurities, remove the crucible and slowly place it in cold water for water cooling. After cooling to room temperature, remove the alloy.

[0062] 2) Homogenization treatment: After the surface of the alloy ingot obtained by melting is polished, it is wrapped with aluminum foil, and then graphite powder is used to completely embed it in a stainless steel crucible. The crucible is placed in a heat treatment furnace, and the temperature is set to rise from room temperature to 300℃ for 2 hours and hold for 1 hour. Then the temperature is raised to 530℃ for 2 hours and held for 12 hours. After the holding period, it is taken out and water-cooled.

[0063] 3) Hot extrusion: The homogenized alloy ingot is machined into cylindrical billets with a diameter of 80mm. The alloy billets and the die are preheated at 420℃ for 2 hours. After preheating, the die and alloy billets are quickly loaded into the extrusion press for positive extrusion. Water cooling is used after extrusion. The extrusion parameters are as follows: Extrusion temperature: 420℃, Extrusion speed: 1.5-2.5 m / min -1 Extrusion ratio: 10.24:1;

[0064] 4) Aging treatment: Cut the bar obtained after hot extrusion into cylindrical bars with a length of 70mm. Wrap the cut bars in aluminum foil and then cover them with graphite. Place them in a crucible and keep them at 200℃ for 26 hours. After the heat treatment is completed, take them out and cool them with water.

[0065] (3) The yield strength of the alloy was 356 MPa and the tensile strength was 385 MPa, as measured by a room temperature tensile mechanical property testing machine.

[0066] Example 2:

[0067] The technical solution of this embodiment is as follows:

[0068] (1) In terms of atomic percentage, the elemental composition of the high-strength rare earth magnesium alloy in this embodiment includes: Ni: 0.75%, Gd: 1.0%, Sm: 0.4%, with the balance being Mg.

[0069] (2) The preparation method of the high-strength rare earth magnesium alloy in this embodiment includes the following process:

[0070] 1) Smelting:

[0071] ① Alloy raw material preparation: The total weight of each batch is 1.5 kg. The burn loss ratio is adjusted according to the type and content range of alloy elements during batching. The raw materials: pure magnesium (99.99 wt.%), Mg-25Ni (wt.%) master alloy, Mg-30Gd (wt.%) master alloy, and Mg-30Sm (wt.%) master alloy are machined into appropriately sized blocks, and the oxide film on the surface is removed with coarse sandpaper. After the alloy is polished to a bright finish, it is packaged in a sealed bag for later use.

[0072] ② Heating the resistance furnace: Set the temperature control program for the resistance furnace, first heat the resistance furnace to 600℃, and after the temperature inside the furnace stabilizes, heat the resistance furnace to 750℃. At the same time, dry and preheat the crucible coated with boron nitride release agent.

[0073] ③ Adding intermediate alloys: After the crucible is completely dried and preheated to above 300℃, place pure magnesium in the crucible and then place the crucible in the resistance furnace, while simultaneously introducing a protective atmosphere of SF6+CO2 (volume ratio of approximately 1:99). After the pure magnesium is completely melted, add the three intermediate alloys Mg-25Ni (wt.%), Mg-30Gd (wt.%), and Mg-30Sm (wt.%) to the stainless steel crucible in sequence. After they are completely melted, adjust the furnace temperature to 730℃ and hold for 10 minutes.

[0074] ④ Stirring and impurity removal: After turning off the power to the resistance furnace, use an electric stirrer to stir from bottom to top for 5 minutes to make the alloy melt as uniform as possible. After the resistance furnace is heated to 720℃ and left to stand for 2 minutes, use a long-handled strainer to filter out impurities.

[0075] ⑤ Cooling: After stirring and removing impurities, take out the crucible and slowly place it in cold water for water cooling. After cooling to room temperature, take out the alloy.

[0076] 2) Homogenization treatment: After the surface of the alloy ingot obtained by melting is polished, it is wrapped with aluminum foil, and then graphite powder is used to completely embed it in a stainless steel crucible. The crucible is placed in a heat treatment furnace, and the temperature is set to rise from room temperature to 300℃ for 2 hours and hold for 1 hour. Then the temperature is raised to 530℃ for 2 hours and held for 12 hours. After the holding period, it is taken out and water-cooled.

[0077] 3) Hot extrusion: The homogenized alloy ingot is machined into cylindrical billets with a diameter of 80mm. The alloy billets and the die are preheated at 420℃ for 2 hours. After preheating, the die and alloy billets are quickly loaded into the extrusion press for positive extrusion. Water cooling is used after extrusion. The extrusion parameters are as follows: Extrusion temperature: 420℃, Extrusion speed: 1.5-2.5 m / min -1 Extrusion ratio: 10.24:1;

[0078] 4) Aging treatment: Cut the bar obtained after hot extrusion into cylindrical bars with a length of 70mm. Wrap the cut bars in aluminum foil and then cover them with graphite. Place them in a crucible and keep them at 200℃ for 26 hours. After the heat treatment is completed, take them out and cool them with water.

[0079] (3) The yield strength of the alloy was 358 MPa and the tensile strength was 390 MPa, as measured by a room temperature tensile mechanical property testing machine.

[0080] Example 3:

[0081] The technical solution of this embodiment is as follows:

[0082] (1) In terms of atomic percentage, the elemental composition of the high-strength rare earth magnesium alloy in this embodiment includes: Ni: 0.75%, Gd: 1.0%, Sm: 0.4%, with the balance being Mg.

[0083] (2) The preparation method of the high-strength rare earth magnesium alloy in this embodiment includes the following process:

[0084] 1) Smelting:

[0085] ① Alloy raw material preparation: The total weight of each batch is 1.5 kg. The burn loss ratio is adjusted according to the type and content range of alloy elements during batching. The raw materials: pure magnesium (99.99 wt.%), Mg-25Ni (wt.%) master alloy, Mg-30Gd (wt.%) master alloy, and Mg-30Sm (wt.%) master alloy are machined into appropriately sized blocks, and the oxide film on the surface is removed with coarse sandpaper. After the alloy is polished to a bright finish, it is packaged in a sealed bag for later use.

[0086] ② Heating the resistance furnace: Set the temperature control program for the resistance furnace, first heat the resistance furnace to 600℃, and after the temperature inside the furnace stabilizes, heat the resistance furnace to 750℃. At the same time, dry and preheat the crucible coated with boron nitride release agent.

[0087] ③ Adding intermediate alloys: After the crucible is completely dried and preheated to above 300℃, place pure magnesium in the crucible and then place the crucible in the resistance furnace, while simultaneously introducing a protective atmosphere of SF6+CO2 (volume ratio of approximately 1:99). After the pure magnesium is completely melted, add the three intermediate alloys Mg-25Ni (wt.%), Mg-30Gd (wt.%), and Mg-30Sm (wt.%) to the stainless steel crucible in sequence. After they are completely melted, adjust the furnace temperature to 730℃ and hold for 10 minutes.

[0088] ④ Stirring and impurity removal: After turning off the power to the resistance furnace, use an electric stirrer to stir from bottom to top for 5 minutes to make the alloy melt as uniform as possible. After the resistance furnace is heated to 720℃ and left to stand for 2 minutes, use a long-handled strainer to filter out impurities.

[0089] ⑤ Cooling: After stirring and removing impurities, take out the crucible and slowly place it in cold water for water cooling. After cooling to room temperature, take out the alloy.

[0090] 2) Homogenization treatment: After the surface of the alloy ingot obtained by melting is polished, it is wrapped with aluminum foil, and then graphite powder is used to completely embed it in a stainless steel crucible. The crucible is placed in a heat treatment furnace, and the temperature is set to rise from room temperature to 300℃ for 2 hours and hold for 1 hour. Then the temperature is raised to 530℃ for 2 hours and held for 12 hours. After the holding period, it is taken out and water-cooled.

[0091] 3) Hot extrusion: The homogenized alloy ingot is machined into cylindrical billets with a diameter of 80mm. The alloy billets and the die are preheated at 420℃ for 2 hours. After preheating, the die and alloy billets are quickly loaded into the extrusion press for positive extrusion. Water cooling is used after extrusion. The extrusion parameters are as follows: Extrusion temperature: 420℃, Extrusion speed: 1.5-2.5 m / min -1 Extrusion ratio: 10.24:1;

[0092] 4) Aging treatment: Cut the bar obtained after hot extrusion into cylindrical bars with a length of 70mm. Wrap the cut bars in aluminum foil and then cover them with graphite. Place them in a crucible and keep them at 200℃ for 26 hours. After the heat treatment is completed, take them out and cool them with water.

[0093] (3) The yield strength of the alloy was 355 MPa and the tensile strength was 396 MPa, as measured by a room temperature tensile mechanical property testing machine.

[0094] Example 4:

[0095] The technical solution of this embodiment is as follows:

[0096] (1) In terms of atomic percentage, the elemental composition of the high-strength rare earth magnesium alloy in this embodiment includes: Ni: 0.75%, Gd: 1.0%, Sm: 0.8%, with the balance being Mg.

[0097] (2) The preparation method of the high-strength rare earth magnesium alloy in this embodiment includes the following process:

[0098] 1) Smelting:

[0099] ① Alloy raw material preparation: The total weight of each batch is 1.5 kg. The burn loss ratio is adjusted according to the type and content range of alloy elements during batching. The raw materials: pure magnesium (99.99 wt.%), Mg-25Ni (wt.%) master alloy, Mg-30Gd (wt.%) master alloy, and Mg-30Sm (wt.%) master alloy are machined into appropriately sized blocks, and the oxide film on the surface is removed with coarse sandpaper. After the alloy is polished to a bright finish, it is packaged in a sealed bag for later use.

[0100] ② Heating the resistance furnace: Set the temperature control program for the resistance furnace, first heat the resistance furnace to 600℃, and after the temperature inside the furnace stabilizes, heat the resistance furnace to 750℃. At the same time, dry and preheat the crucible coated with boron nitride release agent.

[0101] ③ Adding intermediate alloys: After the crucible is completely dried and preheated to above 300℃, place pure magnesium in the crucible and then place the crucible in the resistance furnace, while simultaneously introducing a protective atmosphere of SF6+CO2 (volume ratio of approximately 1:99). After the pure magnesium is completely melted, add the three intermediate alloys Mg-25Ni (wt.%), Mg-30Gd (wt.%), and Mg-30Sm (wt.%) to the stainless steel crucible in sequence. After they are completely melted, adjust the furnace temperature to 730℃ and hold for 10 minutes.

[0102] ④ Stirring and impurity removal: After turning off the power to the resistance furnace, use an electric stirrer to stir from bottom to top for 5 minutes to make the alloy melt as uniform as possible. After the resistance furnace is heated to 720℃ and left to stand for 2 minutes, use a long-handled strainer to filter out impurities.

[0103] ⑤ Cooling: After stirring and removing impurities, take out the crucible and slowly place it in cold water for water cooling. After cooling to room temperature, take out the alloy.

[0104] 2) Homogenization treatment: After the surface of the alloy ingot obtained by melting is polished, it is wrapped with aluminum foil, and then graphite powder is used to completely embed it in a stainless steel crucible. The crucible is placed in a heat treatment furnace, and the temperature is set to rise from room temperature to 300℃ for 2 hours and hold for 1 hour. Then the temperature is raised to 530℃ for 2 hours and held for 12 hours. After the holding period, it is taken out and water-cooled.

[0105] 3) Hot extrusion: The homogenized alloy ingot is machined into cylindrical billets with a diameter of 80mm. The alloy billets and the die are preheated at 420℃ for 2 hours. After preheating, the die and alloy billets are quickly loaded into the extrusion press for positive extrusion. Water cooling is used after extrusion. The extrusion parameters are as follows: Extrusion temperature: 420℃, Extrusion speed: 1.5-2.5 m / min -1 Extrusion ratio: 10.24:1.

[0106] 4) Aging treatment: Cut the bar obtained after hot extrusion into cylindrical bars with a length of 70mm. Wrap the cut bars in aluminum foil and then cover them with graphite. Place them in a crucible and keep them at 200℃ for 26 hours. After the heat treatment is completed, take them out and cool them with water.

[0107] (3) The yield strength of the alloy was 393 MPa and the tensile strength was 417 MPa, as measured by a room temperature tensile mechanical property testing machine.

[0108] Comparative Example 1:

[0109] The technical solution of this embodiment is as follows:

[0110] (1) In terms of atomic percentage, the elemental composition of the high-strength rare earth magnesium alloy in this embodiment includes: Ni: 0.75%, Gd: 1.0%, and the balance is Mg.

[0111] (2) The preparation method of the high-strength rare earth magnesium alloy in this embodiment includes the following process:

[0112] 1) Smelting:

[0113] ① Alloy raw material preparation: The total weight of each batch is 1.5 kg. The burn loss ratio is adjusted according to the type and content range of alloy elements during batching. The raw materials: pure magnesium (99.99 wt.%), Mg-25Ni (wt.%) master alloy, Mg-30Gd (wt.%) master alloy, and Mg-30Sm (wt.%) master alloy are machined into appropriately sized blocks, and the oxide film on the surface is removed with coarse sandpaper. After the alloy is polished to a bright finish, it is packaged in a sealed bag for later use.

[0114] ② Heating the resistance furnace: Set the temperature control program for the resistance furnace, first heat the resistance furnace to 600℃, and after the temperature inside the furnace stabilizes, heat the resistance furnace to 750℃. At the same time, dry and preheat the crucible coated with boron nitride release agent.

[0115] ③ Adding intermediate alloys: After the crucible is completely dried and preheated to above 300℃, place pure magnesium in the crucible and then place the crucible in the resistance furnace, while simultaneously introducing a protective atmosphere of SF6+CO2 (volume ratio of approximately 1:99). After the pure magnesium is completely melted, add the three intermediate alloys Mg-25Ni (wt.%), Mg-30Gd (wt.%), and Mg-30Sm (wt.%) to the stainless steel crucible in sequence. After they are completely melted, adjust the furnace temperature to 730℃ and hold for 10 minutes.

[0116] ④ Stirring and impurity removal: After turning off the power to the resistance furnace, use an electric stirrer to stir from bottom to top for 5 minutes to make the alloy melt as uniform as possible. After the resistance furnace is heated to 720℃ and left to stand for 2 minutes, use a long-handled strainer to filter out impurities.

[0117] ⑤ Cooling: After stirring and removing impurities, take out the crucible and slowly place it in cold water for water cooling. After cooling to room temperature, take out the alloy.

[0118] 2) Homogenization treatment: After the surface of the alloy ingot obtained by melting is polished, it is wrapped with aluminum foil, and then graphite powder is used to completely embed it in a stainless steel crucible. The crucible is placed in a heat treatment furnace, and the temperature is set to rise from room temperature to 300℃ for 2 hours and hold for 1 hour. Then the temperature is raised to 530℃ for 2 hours and held for 12 hours. After the holding period, it is taken out and water-cooled.

[0119] 3) Hot extrusion: The homogenized alloy ingot is machined into cylindrical billets with a diameter of 80mm. The alloy billets and the die are preheated at 420℃ for 2 hours. After preheating, the die and alloy billets are quickly loaded into the extrusion press for positive extrusion. Water cooling is used after extrusion. The extrusion parameters are as follows: Extrusion temperature: 420℃, Extrusion speed: 1.5-2.5 m / min -1 Extrusion ratio: 10.24:1;

[0120] 4) Aging treatment: Cut the bar obtained after hot extrusion into cylindrical bars with a length of 70mm. Wrap the cut bars in aluminum foil and then cover them with graphite. Place them in a crucible and keep them at 200℃ for 26 hours. After the heat treatment is completed, take them out and cool them with water.

[0121] (3) The yield strength of the alloy was 348 MPa and the tensile strength was 367 MPa, as measured by a room temperature tensile mechanical property testing machine.

[0122] Table 1. Elemental composition (at%, atomic percentage) of magnesium alloys in Examples 1-4 and Comparative Example 1.

[0123] Comparative Example 1 0.75 1.0 - margin Example 1 0.75 1.0 0.2 margin Example 2 0.75 1.0 0.4 margin Example 3 0.75 1.0 0.6 margin Example 4 0.75 1.0 0.8 margin

[0124] Table 2 Tensile mechanical properties of magnesium alloys from Examples 1-4 and Comparative Example 1

[0125] Comparative Example 1 348 367 Example 1 356 385 Example 2 358 390 Example 3 355 396 Example 4 393 417

[0126] Please see Figures 2-4 This invention effectively controls the LPSO phase in magnesium alloys by adding Sm elements and combining hot extrusion and heat treatment processes. The number of LPSO phases increases, their size becomes smaller and their distribution becomes more dispersed, and the strength of the magnesium alloy is significantly improved, resulting in high-strength magnesium alloys with yield strength of 356-393 MPa and tensile strength of 385-417 MPa.

[0127] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A preparation process for a high-strength rare-earth magnesium alloy, characterized in that, Includes the following steps: (1) Smelting: Pure magnesium, Mg-25Ni master alloy, Mg-30Gd master alloy, and Mg-30Sm master alloy are smelted into alloy ingots; wherein the purity of the pure magnesium is 99.99 wt.%; the smelting process is carried out under a protective atmosphere of SF6+CO2, and the volume ratio of the protective gas SF6+CO2 is 1:99; the smelting steps include: a) Alloy raw material preparation: pure magnesium, Mg-25Ni master alloy, Mg-30Gd master alloy and Mg-30Sm master alloy are machined into blocks and the oxide film on their surface is ground off. b) Heating the resistance furnace: First, heat the resistance furnace to 600℃, and after the temperature stabilizes, heat it to 750℃. At the same time, dry and preheat the crucible. c) Adding intermediate alloys: After the crucible is preheated to above 300°C, pure magnesium is placed in the crucible and the crucible is placed in the resistance furnace. Protective gas SF6+CO2 is introduced. After the pure magnesium melts, Mg-25Ni, Mg-30Gd and Mg-30Sm intermediate alloys are added in sequence. After they are completely melted, the furnace temperature is adjusted to 730°C and held for 10 minutes. d) Stirring and impurity removal: After power is off, stir for 5 minutes, then heat the resistance furnace to 720°C, let it stand for 2 minutes, and then use a long-handled strainer to filter out the impurities. e) Cooling: Remove the crucible and place it in cold water to cool to room temperature, then remove the alloy ingot; (2) Homogenization treatment: After the surface of the alloy ingot is polished, it is wrapped with aluminum foil, then graphite powder is embedded in the crucible, and the crucible is placed in a heat treatment furnace. The temperature is raised to 300℃ and held for 1 hour, then raised to 530℃ and held for 12 hours. After the holding is completed, it is water-cooled. The time to raise the temperature to 300℃ is 2 hours, and the time to raise the temperature to 530℃ is 2 hours. (3) Hot extrusion: The homogenized alloy ingot is processed into a cylindrical billet with a diameter of 80mm, and preheated together with the die at a temperature of 420℃ for 2 hours. Then, it is loaded into the extrusion press for positive extrusion. The extrusion parameters are: extrusion temperature 420℃, extrusion speed 1.5-2.5m·min -1 The extrusion ratio is 10:24:1, and the material is water-cooled after extrusion. (4) Aging treatment: Cut the hot-extruded bar into cylindrical bars with a length of 70mm, wrap them with aluminum foil, bury them in a crucible with graphite powder, and keep them at 200℃ for 26 hours. After the heat preservation is completed, cool them with water. The alloy composition of the alloy ingot contains the following atomic percentages: Ni: 0.75%, Gd: 1.0%, Sm: 0.2-0.8%, with the remainder being Mg.

2. A high-strength rare-earth magnesium alloy, characterized in that, The alloy is prepared by the preparation process described in claim 1, and the atomic percentages of each element in its composition are: Ni: 0.75%, Gd: 1.0%, Sm: 0.2-0.8%, with the remainder being Mg.

Citation Information

Patent Citations

  • Nickel-containing heat resisting magnesium-rare earth alloy and preparation method thereof

    CN101392345A